3D printing dual-scale roughness tri-periodic extremely-small curved surface structure battery current collector and preparation method thereof

The copper current collector with a three-period extremely small curved surface structure with double-scale roughness is fabricated through selective laser melting 3D printing technology, which solves the problems of uncontrollable growth and volume changes of lithium dendrites, and achieves efficient and stable lithium metal anode performance.

CN119890318APending Publication Date: 2025-04-25WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510084364.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Lithium metal batteries have battery failure due to the uncontrollable growth and volume changes of lithium dendrites, which pose safety hazards, low Coulomb efficiency and reduced battery capacity.

Method used

Selective laser melting 3D printing technology is used to manufacture copper current collectors with three-periodic extremely small curved surface structures with double-scale roughness, and the polished top surface and rough inner cavity are achieved through post-treatment steps to inhibit the formation of lithium dendrites.

Benefits of technology

Effectively inhibit the formation of lithium dendrites, adapt to volume expansion during the cycle, and improve the overall stability of the lithium metal anode. The Coulomb efficiency is as high as 98%, and the capacity reaches 154mAh g-1, showing a low overpotential and a long cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890318A_ABST
    Figure CN119890318A_ABST
Patent Text Reader

Abstract

The invention discloses a 3D printing dual-scale roughness three-periodicity extremely-small curved surface structure battery current collector and a preparation method thereof, a selective laser melting three-dimensional printing technology is utilized to manufacture a three-dimensional copper current collector, and then the dual-scale roughness is realized through a post-processing step. The resulting P-Cu-GLS has a polished top surface and a roughened inner cavity, improving the deposition of lithium by promoting uniform nucleation and growth of lithium within the cavity. The structure modification can effectively inhibit the formation of dendritic crystals, adapts to volume expansion in the cycle process, and improves the overall stability of the lithium metal anode. The invention embodies the multifunctionality of the selective laser melting printing three-dimensional current collector with customized surface roughness as an advanced strategy of a lithium metal anode. The simplicity and expandability of the method show that the method can be widely applied to other metal-based energy storage systems, and paves a way for a safer and more efficient battery technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of battery current collectors, and in particular relates to a 3D printed dual-scale roughness three-periodic minimal surface structure battery current collector and a preparation method thereof. Background Art

[0002] There are many metal-based batteries similar to lithium metal, all of which have the problem of uncontrollable growth of dendrites, so we need to make efforts in this regard and improve the batteries. The manufacturing method involved in the present invention is applicable to metal-based batteries of various materials and current collectors of various three-period minimal surface structures. The lithium battery with copper as the current collector will be described in detail below, but the method and structure of the invention design are not limited to this material and structure.

[0003] With the widespread use of electric vehicles, mobile devices and smart wearable devices in daily life, lithium-ion batteries play a vital role as energy storage devices. Compared with graphite anode, the theoretical specific capacity of metallic lithium is 3861mAhg -1 , which is about 10 times higher than that of graphite. In addition, metallic lithium also has a low redox potential of -3.04 V (compared with the standard hydrogen potential electrode) and a carbon dioxide concentration of 0.53 g cm -3 All these properties make metallic lithium the "holy grail" of negative electrodes in lithium-ion battery systems.

[0004] However, the ownerless nature of lithium metal, the uncontrollable growth of lithium dendrites, and the significant volume changes of lithium metal anodes during battery cycling lead to battery failure. Since the metal lithium cannot maintain ion deposition during deposition and stripping, the morphology of lithium is difficult to control, resulting in unpredictable volume expansion and contraction of lithium during battery operation. During long-term cycling, lithium dendrites can easily fall off the current collector and become electrochemically inactive "dead lithium". The above problems of lithium metal anodes can lead to safety hazards, low Coulombic efficiency, and reduced battery capacity.

[0005] Therefore, great efforts have been made to solve the problems associated with lithium metal. Among them, the construction of three-dimensional lithium anode, such as housing the lithium anode in a three-dimensional current collector, is considered to be an effective strategy to solve the problem of uncontrollable growth of lithium dendrites caused by the host-less nature of lithium metal. The lithium anode with a large specific surface area structure induces a uniform electric field distribution, which contributes to the uniform nucleation of lithium and reduces the growth of dendrites. Summary of the invention

[0006] To solve the above problems, we propose a selective laser melting 3D printing dual-scale roughness three-periodic minimal surface structure battery current collector and its preparation method, which is used to produce a copper current collector with a dual-scale roughness structure to prevent the growth of lithium dendrites. Combining the advantages of free design and high resolution of selective laser melting 3D printing, we introduced a triple periodic minimal surface structure in the design of lithium-ion battery current collectors. The three-dimensional copper current collector printed by selective laser melting in the present invention has a dual-scale roughness three-periodic minimal surface structure, which can effectively alleviate the growth of lithium dendrites and the volume change during lithium plating and stripping.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a 3D printed dual-scale roughness three-periodic minimal surface structure battery current collector comprises the following steps:

[0009] Step 1: Use a selective laser melting 3D printer to print metal powder into a periodic curved surface structure, wherein the periodic curved surface structure includes a plurality of periodically arranged unit cells, wherein the unit cell is a tri-periodic minimal surface structure, and the size of the unit cell is (1.5-3)×(1.5-3)×(1.5-3) mm 3 ;

[0010] Step 2: Polish the surface of the periodic curved surface structure to form a dual-scale roughness with a smooth top surface and a rough inner cavity, thereby obtaining a battery current collector with a three-periodic minimal curved surface structure.

[0011] Furthermore, in step 1, the tri-periodic minimal surface structure adopts any one of a Gyroid structure, a Schwarz structure, a Diamond structure, a Lidinoid structure, a Neovius structure or a Splitp structure.

[0012] Furthermore, in step 1, the periodic curved surface structure is in the shape of a disk with a diameter of 15-18 mm.

[0013] Furthermore, in step 2, the periodic curved surface structure is polished for 1-2 minutes using sandpaper with a mesh size of 500 to 2000.

[0014] The 3D printed dual-scale roughness three-periodic minimal surface structure battery current collector is prepared by the above method.

[0015] The present invention has the following beneficial technical effects:

[0016] This paper discloses a new strategy to fabricate 3D copper current collectors using selective laser melting 3D printing technology, followed by a post-processing step to achieve dual-scale roughness. The resulting 3D current collector has a polished top surface and a rough inner cavity, which improves lithium deposition by promoting uniform nucleation and growth of lithium in the cavity. This structural modification can effectively inhibit the formation of dendrites, accommodate volume expansion during cycling, and improve the overall stability of the lithium metal anode. This current collector with dual-roughness 3D structure has a good performance at 1mA cm in half-cell. -2 The Coulombic efficiency is as high as 98% under the condition of full battery 1C, and the capacity reaches 154mAh g -1 , showing lower overpotential and longer cycle life. In addition, its rate performance is also improved, with a capacity of 120 mAh g at 5C. -1 , which further highlights its potential in high-performance lithium metal batteries.

[0017] This invention demonstrates the versatility of selective laser melting-printed 3D current collectors with tailored surface roughness as an advanced strategy for lithium metal anodes. The simplicity and scalability of this method suggest that it can be widely applied to other metal-based energy storage systems, paving the way for safer and more efficient battery technologies. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic diagram of the Gyroid structure;

[0019] Figure 2 It is a schematic diagram of the Schwarz structure;

[0020] Figure 3 This is a schematic diagram of the Diamond structure;

[0021] Figure 4 It is a schematic diagram of Lidinoid structure;

[0022] Figure 5 This is a schematic diagram of the Neovius structure;

[0023] Figure 6 It is a schematic diagram of the Splitp structure;

[0024] Figure 7 This is a schematic diagram of the finite element modeling results using Comsol Multiphasics 6.0 software;

[0025] Figure 8 A schematic diagram of the process of preparing a three-dimensional current collector by selective laser melting and selective polishing according to the present invention;

[0026] Fig. 9 The design size of the image (a) is 2×2×2mm3 Unit cell diagram, (b) atlas fluid modeling diagram;

[0027] Fig.10 (a) and (b) are optical images of Cu-GLS with rough top surface and inner cavity, (c) and (d) are optical images of P-Cu-GLS with smooth top surface and rough inner cavity; the scale bars in (a) and (c) are 2 mm; the scale bars in (b) and (d) are 0.5 mm;

[0028] Fig.11 The surface roughness (Ra) value distribution diagram of the two samples;

[0029] Fig.12 SEM images of the morphology of different lithium deposition amounts on different current collectors are shown in Figure 1. (a) shows the Cu-GLS current collector before lithium deposition; (b) shows the Cu-GLS current collector after lithium deposition of 1 mAh cm -2 Cu-GLS current collector after deposition; (c) shows lithium deposition of 5 mAh cm -2 (d) shows the P-Cu-GLS current collector before lithium deposition, and (e) shows the 1 mAh cm -2 P-Cu-GLS current collector after lithium deposition, (f) 5 mAh cm -2 P-Cu-GLS current collector after lithium deposition;

[0030] Fig.13 is a voltage curve diagram of a battery using P-Cu-GLS;

[0031] Fig.14 is a voltage curve diagram using a planar copper battery;

[0032] Fig.15 Nucleation overpotential diagram of batteries based on Cu-GLS and P-Cu-GLS;

[0033] Fig.16 Coulombic efficiency diagram of P-Cu-GLS-based battery over 200 cycles;

[0034] Fig.17 Schematic diagram of different lithium deposition behaviors on planar copper foil, Cu-GLS and P-Cu-GLS;

[0035] Fig.18 This is a graph of the discharge capacity of a battery using bare lithium metal;

[0036] Fig.19 The discharge capacity diagram of the battery using Li@Cu-GLS;

[0037] Fig. 20The discharge capacity diagram of the battery using Li@P-Cu-GLS;

[0038] Fig.21 Schematic diagram of the capacity and CE of the Li@Cu-GLS battery after 130 cycles;

[0039] Fig. 22 Rate performance plots for cells with three different anode configurations. DETAILED DESCRIPTION

[0040] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0041] All three-periodic minimal surface structures are applicable to the present invention, including Gyroid, Schwarz, Diamond, Lidinoid, Neovius, Splitp, etc. The invented 3D current collector is applicable to all metal batteries. The present invention is described in detail below by example. In this embodiment, a gyroid structure is used to prepare a copper metal current collector. The manufacturing process and method of the present invention are applicable to the production of all metal current collectors. Schematic diagrams of various structural surfaces of three-periodic minimal surfaces are shown in FIG. Figure 1-6 shown.

[0042] The preparation and testing process of this embodiment are as follows:

[0043] Preparation of three-dimensional copper current collector: Commercial copper powder (purity 99.9%, particle size 15-53 μm) was obtained from Beijing Longbang New Material Technology Co., Ltd. The copper powder was printed using a German 200R concept laser laboratory with a laser power of 180 watts and a scanning speed of 200 mm / s. The resulting current collector was then polished using sandpaper (with particle sizes ranging from 500 to 2000) and subsequently cleaned with alcohol.

[0044] Electrochemical measurements: CR2030 coin cells were assembled in a glove box. Asymmetric cells were assembled with various Cu current collectors as working electrodes, lithium metal as counter electrode, 1 wt% LiNO3 in DOL (1,3-dioxane) / DME (1,2-dimethoxyethane) (1:1 by volume) as electrolyte (DodoChem, China), and Whatman 1823 glass fiber (Whatman, UK) as separator. For activation, the cells were initially cycled between 0 and 1 V (vs Li+ / Li) at 50 μA for 5 times. After activation, the cells were charged at a current density of 1 mA cm -2 A certain amount of Li (1 mAh cm) is plated on the collector. -2 ), and peel towards 1.0V, cycling the battery.

[0045] In the full battery test, lithium iron phosphate (LFP) was used as the cathode, and bare lithium (Li) metal or various 3D Cu current collector / Li composite materials were used as the anode. The electrolyte was composed of 1M lithium hexafluorophosphate (LiPF6) mixed with dimethyl carbonate (DMC), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1, and 1% ethylene carbonate (VC) was used as an additive. Celgard2325 (Celgard, USA) was used as a separator. In NMP (n-methyl-2-pyrrolidone) solvent, LFP powder, super phosphorus and binder PVDF (wt.% 8:1:1) were first mixed to prepare the LFP cathode. The resulting uniform slurry was then cast on aluminum foil and dried in a vacuum oven at 80°C overnight. Five constant current cycles were performed at 0.2C between 2.5V and 3.8V (vs.Li+ / Li), followed by subsequent cycles at 1c. For rate testing, cells were cycled at 0.2, 1, 2, and 5°C.

[0046] Scanning electron microscopy analysis: Scanning electron microscopy analysis was performed using a field emission scanning electron microscope (FESEM, NOVA400NanoSEM, FEI, USA) at 10 kV. After lithium deposition, the asymmetric cells were disassembled in a glove box. The obtained CCs were washed with DEC water to remove the remaining electrolyte and lithium salts.

[0047] Surface morphology characterization: The surface profile height map was scanned using a profilometer (VR6000, TA, USA) at magnifications of 12, 40, and 80. The upper and lower surface roughness before and after polishing was measured using the analysis software included with the profilometer.

[0048] Theoretical simulation: Comsol Multiphasics 6.0 software was used for finite element modeling (FEM) to study the current density distribution of different current collectors. The electrodeposition model was selected, the Nernst-Planck equation was used to track the mesh deformation, and the Butler-Volmer equation was used to represent the electrochemical reaction kinetics of the deposition process. COMSOL Multiphysics was used to simulate the current density distribution during lithium deposition to verify the deposition behavior on Cu-GLS and P-Cu-GLS current collectors. Figure 7 As shown in Figure (a), in the case of Cu-GLS, the results show that the current density is mainly concentrated on the rough top surface, while the current density in the internal cavity remains small. This uneven distribution promotes the deposition of lithium on the top surface, resulting in dendritic growth. In contrast, when the top surface of P-Cu-GLS is polished, the current density on the surface is significantly reduced due to the reduction of surface roughness, as shown in Figure 2. Figure 7 At the same time, the current density in the rough cavity becomes significantly higher, as shown in Figure (b). Figure 7Middle (c)-(d). These holes provide many protruding tips that serve as favorable nucleation sites, promoting the uniform growth of lithium inside the holes. This behavior illustrates the effectiveness of the inner cavity structure in P-Cu-GLS, which not only guides lithium deposition inwards but also helps to reduce the formation of dendrites, ensuring a more stable and uniform deposition process.

[0049] Figure 8 The process of preparing a 3D metal current collector with dual-scale roughness by selective laser melting and selective polishing is demonstrated. First, the laser emitter emits a laser beam to irradiate the molding chamber, and the high-temperature laser beam is scanned in the molding chamber to melt the powder, and then stacked layer by layer to form a solid body to produce a metal current collector. Then the successfully prepared current collector is taken out and selectively polished using physical methods until the surface is smooth. Selective polishing means that only the surface is polished, while the inner surface maintains the original roughness. In this study, pure copper powder with a particle size range of 15-53μm was used as the raw material for selective laser melting processing. The copper frame is designed to be a disc with a diameter of 15.8mm. This structure is based on a repeatedly arranged gyroid lattice to form a TPMS structure, which can be defined by the following expression:

[0050]

[0051] Where x, y, z are spatial coordinates, and l is the unit cell length. The unit size designed in this work is 2×2×2mm 3 Fig. 9 Middle (a). The Gyroid unit cell is replicated symmetrically along each coordinate direction (X, Y, and Z), forming a continuous and interconnected network that can be used as a current collector with a higher specific surface area and optimized conductivity, making it a viable option for lithium metal anodes with a diameter of 16 mm.

[0052] Fig.10 Figures (a) and (b) show the printed copper frame (called Cu-GLS), which is consistent with the expected design and presents a continuous interconnected unit cell network of a typical gyro lattice structure. As shown in Figures (c) and (d), after the selective laser melting process, the printed copper frame is selectively polished to form a dual-scale roughness, namely P-Cu-GLS, which is characterized by a smooth top surface and a rough inner cavity.

[0053] The distribution of surface roughness (Ra) values ​​of the two samples is shown in Fig.11 , showing an average Ra value of 15.2 μm for the inner cavity. The top surfaces of Cu-GLS and P-Cu-GLS show lower Ra values ​​of 10.7 μm and 0.5 μm, respectively. It is worth noting that the top surface of Cu-GLS shows lower roughness than the inner cavity despite the lack of polishing. Fig.10As shown, the roughness value of the P-Cu-GLS surface is significantly lower and more consistent, with minimal surface undulations, indicating that polishing can produce a smooth and flat surface. The dramatic surface undulations and roughness fluctuations of Cu-GLS indicate that its surface is more irregular and rougher, while the stable and low roughness values ​​of P-Cu-GLS reflect the refined surface after polishing. These results demonstrate the feasibility of fabricating a three-dimensional copper current collector with a typical three-periodic minimal surface gyro lattice structure with dual-scale roughness.

[0054] In order to intuitively compare the deposition behavior of lithium in three-dimensional current collectors with different surface morphologies, scanning electron microscopy was used to study the surface morphology of lithium in the 1 mAh cm -2 Up to 5 mAh cm -2 The morphology of lithium deposited on Cu-GLS and P-Cu-GLS current collectors at different current densities. Fig.12 As shown in Figures (a) and (c), during lithium deposition, the thickness of the upper surface of the Cu-GLS current collector varies greatly, while the internal cavity is basically not filled, and lithium tends to be preferentially deposited on the upper surface of the Cu-GLS current collector rather than in the internal cavity. This deposition pattern may be attributed to the roughness of the upper surface, which is conducive to the uneven accumulation of lithium and leads to the formation of obvious bulges, especially when the deposition amount reaches 5 mAh cm -2 Therefore, the Cu-GLS current collector loses the ability to effectively regulate the current distribution and cannot suppress the growth of dendrites. In contrast, the P-Cu-GLS current collector clearly shows that lithium is preferentially deposited in the inner cavity with a rough surface and extends toward the smooth upper surface until the inner cavity is filled, as shown in Figure 2. Fig.12 Middle (d)-(f). This behavior demonstrates the functional advantage of a 3D current collector, as this structure provides optimal cavities that promote uniform nucleation and growth of lithium, thereby effectively preventing lithium aggregation and dendrite formation.

[0055] To investigate the lithium deposition behavior in 3D current collectors, planar copper foil, Cu-GLS, and P-Cu-GLS were assembled with lithium foil into half-cells and charged at 1 mA cm -3 The current density and 1 mAh cm -2 The hysteresis voltage is a key parameter of the voltage difference during charge and discharge, reflecting the polarization behavior of the electrode. Fig.13 The voltage curve of the battery using P-Cu-GLS is shown, which shows that the battery can still maintain a stable hysteresis voltage of 26mV after 150 cycles. This performance is better than that of planar copper batteries (see Fig.13 ), the latter has a hysteresis voltage of 42mV after 150 cycles. Fig.15As shown in Figure 2, the nucleation overpotentials of the cells based on Cu-GLS and P-Cu-GLS are 20mV and 23mV, respectively. In contrast, the nucleation overpotential of the cell using planar copper is as high as 64mV due to the lack of a larger surface area or additional nucleation sites. The cell based on P-Cu-GLS has a lower nucleation overpotential because the 3D framework has a higher specific surface area, providing more space for lithium deposition.

[0056] Coulombic efficiency (CE) is another key parameter to evaluate the lithium plating / stripping stability of the current collector. Fig.16 As shown, the CE of the P-Cu-GLS-based battery remains at 98% for 200 cycles. The low CE values ​​and poor cycling stability of the batteries using Cu-GLS may be due to the uneven lithium nucleation occurring on the rough top surface rather than the inner cavity, which accelerates the formation of lithium dendrites and dead lithium. These findings confirm that the printed Cu-GLS has a larger surface area and can significantly reduce the nucleation resistance of lithium. In addition, we also introduced a dual-scale roughness structure through post-treatment, which has abundant protrusions that can act as nucleation sites to promote uniform deposition of lithium. These characteristics help to achieve highly reversible lithium plating and stripping, thereby developing high-capacity and stable lithium metal anodes.

[0057] Fig.17 Schematic diagrams of different lithium deposition behaviors on planar copper foil, Cu-GLS, and P-Cu-GLS are provided. In the case of copper foil, lithium tends to first form small lithium dendrites on the smooth surface during the nucleation step. These initial dendrites act as charge centers in the electric field, accumulating charges at their sharp tips, see Fig.17 Middle (a). The subsequent lithium deposition occurs mainly at the tips, accelerating the dendrite growth.

[0058] On the contrary, the performance of 3D printed current collectors is expected to be improved due to the increased specific surface area of ​​the porous structure, which reduces the local current density and enhances the deposition of lithium in the internal cavities. However, the rough surface of Cu-GLS provides many protruding tips that serve as charge centers and nucleation sites, resulting in lithium nucleation and growth mainly on the surface instead of filling the internal cavities of the 3D collector, thus promoting dendritic growth, see Fig.17 Middle (b) figure.

[0059] In contrast, the top surface of P-Cu-GLS is smoother, eliminating the protruding tips on the outer surface. At the same time, these protruding tips remain in the inner cavities, thereby promoting the deposition of lithium in these cavities and forming a more uniform lithium surface, such as Fig.17 This change not only improves the volume utilization of P-Cu-GLS, but also enhances the structural integrity of the deposited lithium, thereby alleviating the problem of dendritic growth.

[0060] To evaluate the practical applicability of 3D printed current collectors, we conducted cycling tests on full cells with bare lithium metal, Li@Cu-GLS or Li@P-Cu-GLS as anodes and LFP cathodes. Figure 17-19 As shown, the battery using Li@Cu-GLS can provide 153.5mAh g -1 The capacity is comparable to that of the battery using Li@P-Cu-GLS (148.1mAhg -1 ) is equivalent to that of bare lithium batteries (134.9mAh g -1 After 100 cycles, the discharge capacities of Li@Cu-GLS and Li@P-Cu-GLS batteries are still 160 mAh g -1 and 154mAh g -1 , due to the large specific surface area and conductive network of the 3D framework current collector, it exhibits stronger cycling stability. However, the capacity and CE of the Li@Cu-GLS battery rapidly decrease after 130 cycles ( Fig.21 ), which may be due to the internal short circuit caused by lithium dendrites. In contrast, the Li@P-Cu-GLS battery showed excellent cycling stability and provided 157.28 mAh g after 250 cycles. -1 The reversible capacity of the battery is about 100%, the capacity retention rate is about 100%, and the CE is 98.1%.

[0061] In addition, we tested the rate performance of cells with three different anode configurations, e.g. Fig. 22 As shown in Figure 2, the batteries using the 3D framework, namely Li@Cu-GLS and Li@P-Cu-GLS, show higher rate capabilities than those using bare lithium metal. It is worth noting that the battery using Li@P-Cu-GLS has a capacity of 140 mAh g at high rates of 2C and 5C, respectively. -1 and 120mAh g -1 , better than bare lithium battery (125mAh g -1 and 108mAh g -1 The above results indicate that this P-Cu-GLS is beneficial for improving the cycling stability and rate capability of Li metal batteries, indicating that it is a feasible Li metal anode current collector for practical applications.

[0062] The above is an example of the best implementation of the present invention, and the parts not described in detail are common knowledge of ordinary technicians in the field. The protection scope of the present invention shall be based on the content of the claims, and any equivalent transformation based on the technical enlightenment of the present invention is also within the protection scope of the present invention.

Claims

1. A method for preparing a 3D printed dual-scale roughness three-periodic minimal surface structure battery current collector, characterized in that: The following steps are involved: Step 1: Use a selective laser melting 3D printer to print metal powder into a periodic curved surface structure, wherein the periodic curved surface structure includes a plurality of periodically arranged unit cells, wherein the unit cell is a tri-periodic minimal surface structure, and the size of the unit cell is (1.5-3)×(1.5-3)×(1.5-3) mm 3 ; Step 2: Polish the surface of the periodic curved surface structure to form a dual-scale roughness with a smooth top surface and a rough inner cavity, thereby obtaining a battery current collector with a three-periodic minimal curved surface structure.

2. The method for preparing a 3D printed dual-scale roughness three-periodic minimal surface structure battery current collector according to claim 1, characterized in that: In the step 1, the tri-periodic minimal surface structure adopts any one of a Gyroid structure, a Schwarz structure, a Diamond structure, a Lidinoid structure, a Neovius structure or a Splitp structure.

3. The method for preparing a 3D printed dual-scale roughness three-periodic minimal surface structure battery current collector according to claim 1, characterized in that: In the step 1, the periodic curved surface structure is in the shape of a disk with a diameter of 15-18 mm.

4. The method for preparing a 3D printed dual-scale roughness three-periodic minimal surface structure battery current collector according to claim 1, characterized in that: In the step 2, the periodic curved surface structure is polished for 1-2 minutes using 500 to 2000 mesh sandpaper. 5.3D printed dual-scale roughness three-periodic minimal surface structure battery current collector, characterized by: Prepared by the method according to any one of claims 1 to 4.